IVAN CANKAR V MEDKULTURNEM PROSTORU. OB STOTI OBLETNICI CANKARJEVE SMRTI: Maribor: Univerzitetna založba Univerze, 2018 (Mednarodna knjižna zbirka Zora, 126). 430 str. - Belšak, Silva (Slavia Centralis, 2020)
The article presents the scientific monograph Ivan Cankar v medkulturnem prostoru (Ivan Cankar in the Intercultural Space), which was created in Cankar’s year 2018 on the centenary of the writer’s death. It was edited by dr. Jožica Čeh Steger, dr. Simona Pulko and dr. Melita Zemljak Jontes from the Department of Slavic Languages ​​and Literatures, Faculty of Arts, University of Maribor.